THEORETICAL SCIENCE IN MUNASABAH DISCURSE: DISCOVERING MOUNTAIN FACTS IN THE QURAN - Prakoso, Theo Jaka (Journal of Islam and Science, 2019)
This research presents the Qur'an as a source of knowledge (in the perspective of munasabah science), so that it becomes a motivation for Muslims to explore the wonders of the Qur'an with various approaches, especially using the theoretical science. The holy messages of God's revelation can be captured rationally and scientifically as modern research is developing. Muslim scholars matched many scientific studies with the Qur'an statements which had taken place 1400 years ago. They find many surprising facts that the physical mountain according to modern geology shows the mountain as a peg or nail of the earth serves to strengthen the existence of the earth, has been hinted by the Prophet Muhammad through the glorious Qur'an. This has proven that the Qur'an is not only seen as a mere doctrinal book, but a holy book that can be proven with the scientific method and scientific facts in the field.